2018
DOI: 10.3389/fphys.2018.00846
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intensity During Cross-Country Skiing Described by Oxygen Demands in Flat and Uphill Terrain

Abstract: Purpose: In this study wearable global navigation satellite system units were used on athletes to investigate pacing patterns by describing exercise intensities in flat and uphill terrain during a simulated cross-country ski race.Methods: Eight well-trained male skiers (age: 23.0 ± 4.8 years, height: 183.8 ± 6.8 cm, weight: 77.1 ± 6.1 kg, VO2peak: 73 ± 5 mL⋅kg-1⋅min-1) completed a 13.5-km individual time trial outdoors and a standardized indoor treadmill protocol on roller skis. Positional data were recorded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 42 publications
(73 reference statements)
7
72
1
Order By: Relevance
“…Many previous studies have shown that higher work rates are obtained on uphill terrain in XC skiing during actual and simulated competitions. 4,[6][7][8][9][10][11][12]14,16 However, this study provides additional information about XC skiers' ability to generate WRmax in flat and uphill skating on snow, and the percentage of WRmax achieved in both terrains during LIT, MIT and HIT. Specifically, the skiers reached ~595 W (7.75 W•kg -1 ) with the G2-skating technique on uphill terrain, which is 80% greater than the ~326 W (4.23 W•kg -1 ) performed with the G3-skating technique on the flat.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many previous studies have shown that higher work rates are obtained on uphill terrain in XC skiing during actual and simulated competitions. 4,[6][7][8][9][10][11][12]14,16 However, this study provides additional information about XC skiers' ability to generate WRmax in flat and uphill skating on snow, and the percentage of WRmax achieved in both terrains during LIT, MIT and HIT. Specifically, the skiers reached ~595 W (7.75 W•kg -1 ) with the G2-skating technique on uphill terrain, which is 80% greater than the ~326 W (4.23 W•kg -1 ) performed with the G3-skating technique on the flat.…”
Section: Discussionmentioning
confidence: 99%
“…This has previously been reported by Bolger et al 4 in world-class skiers during distance races across varying terrain, and although this effect is clearly greater at high intensities, we here show that it is present during all the endurance training intensities. The greater effect of the delayed HR response during HIT is due to the fact that work rates exerted in the uphill terrain drives the intensity above maximal oxygen uptake 6,9,11 and causes oxygen deficit, which eventually leads to an additionally increase in HR in the subsequent terrain. This gives less opportunity for recovery, resulting in a relatively higher and more stable HR throughout the course during HIT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations